First Nations women carvers: Celebrating creation and creativity. - Siermacheski, Catherine (Author); Mills, Antonia (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2005)
This thesis represents my journey of discovery to learn about the role of First Nations women carvers in today's First Nations societies in the Northern Northwest-Central region of British Columbia. It is based on learning about the creative world of five First Nations Women carvers: Pauline Allan of the Carrier Nation, Valerie Morgan and her sister Virginia Morgan, born into the Kwakwaka'wakw Nation and Gitxsan on their father's side and by marriage, Dale Campbell of the Tahltan Nation, and Victoria Moody of the Haida Nation. What I learned from these women illuminated the concepts of what is traditional and what is contemporary and taught me that my queries about gender disparity, exhibitions, sales and success were coming from a very Western perspective. I use the words the women told me to show their perception that being a First Nations woman is not about breaking down barriers of gendered roles but a means for them to revitalize their traditions. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1288565